2004
DOI: 10.1109/tkde.2004.29
|View full text |Cite
|
Sign up to set email alerts
|

Multistrategy ensemble learning: reducing error by combining ensemble learning techniques

Abstract: Ensemble learning strategies, especially Boosting and Bagging decision trees, have demonstrated impressive capacities to improve the prediction accuracy of base learning algorithms. Further gains have been demonstrated by strategies that combine simple ensemble formation approaches. In this paper, we investigate the hypothesis that the improvement in accuracy of multi-strategy approaches to ensemble learning is due to an increase in the diversity of ensemble members that are formed. In addition, guided by this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
107
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(109 citation statements)
references
References 10 publications
2
107
0
Order By: Relevance
“…It also offers the further advantage over AdaBoost of suiting parallel execution. MultiBoosting has been further extended by adding the stochastic attribute selection committee learning strategy to boosting and wagging [180]. The latter's research has shown that combining ensemble strategies would increase diversity at the cost of a small increase in individual test error resulting in a trade-off that reduced overall ensemble test error.…”
Section: Multistrategy Ensemble Learningmentioning
confidence: 99%
“…It also offers the further advantage over AdaBoost of suiting parallel execution. MultiBoosting has been further extended by adding the stochastic attribute selection committee learning strategy to boosting and wagging [180]. The latter's research has shown that combining ensemble strategies would increase diversity at the cost of a small increase in individual test error resulting in a trade-off that reduced overall ensemble test error.…”
Section: Multistrategy Ensemble Learningmentioning
confidence: 99%
“…Due to the different approaches applied to generate the committee, the decision trees in the final ensemble committee could be diverse from each other in certain ways. In the past decades, measuring diversity has become a very important issue in the research of Microarray ensemble classification methods [1,5,9].…”
Section: Measurement Of Diversitymentioning
confidence: 99%
“…There are also many statistical diversity measures available, such as diversity of errors [1,2,7], and pairwise and non-pairwise diversity measures [1,9,5]. It is desirable if every classifier in an ensemble committee can agree on most samples which are predicted correctly.…”
Section: Measurement Of Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…This flexibility in theory results in over fitting the training data than a single model. But, the practical ensemble techniques tend to reduce over fitting of the training data [3].…”
Section: Introductionmentioning
confidence: 99%